DEVELOPMENT OF ALGORITHM FOR SYNTHETIC NATURAL GAS FOR VEHICLES (SNGV) PRODUCTION FROM EMPTY FRUIT BUNCHES - AMMAR, MUHAMMAD (2018)
The world energy demand is increasing with the rapid growth of industrialization and the simultaneous growth in population. Due to contemporary energy crisis and environmental impact associated with the utilization of fossil, the production of synthetic natural gas for vehicles (SNGV) from thermochemical processing of oil palm waste offers excellent potential to diminish the dependency on fossil fuel in transportation sector. In the current study, a systematic algorithm is designed integrated with reaction kinetic model, flow sheet model, and economics to evaluate the optimum parameters for the production of SNGV.